A novel approach indirectly comparing benefit–risk balance across anti-thrombotic therapies in patients with atrial fibrillation. Issue 1 (2nd January 2015) - Dogliotti, Ariel; Giugliano, Robert P.
Abstract : Background: Anti-thrombotic reduces thromboembolic events but increases bleeding in patients with atrial fibrillation (AF). We evaluated the benefit–risk of anti-platelet and anti-coagulant therapies, weighing these conflicting effects of treatment. Methods: Randomized controlled trials in patients with AF were identified from MEDLINE, Embase, and Cochrane Central Register of Controlled Trials through April 2014. We performed a stochastic multi-criteria acceptability analysis, which allowed us to compute a comprehensive benefit–risk profile. In the primary analysis, we used prior established rankings of mortality, intracranial haemorrhage, ischaemic stroke, myocardial infarction, major extracranial haemorrhage, and systemic embolism based on utility functions. In sensitivity analyses, we explored: (i) rankings based on costs, (ii) bleeding ranked higher than thromboembolism, and (iii) thromboembolism ranked higher than bleeding events. Results: 100 913 patients (21 studies) were allocated to placebo/control, aspirin and/or clopidogrel, vitamin K antagonists (VKAs), or new oral anti-coagulants (NOACs). Based on utility, NOACs were better than VKA or anti-platelet therapy; dabigatran 150 mg was ranked highest (21% chance of being best). Ranked by cost, the 3 factor Xa inhibitors were very similar (16–18% chance of being best). When haemorrhagic events were weighted more than ischaemic events, edoxaban 30 mg was ranked higher (22%), while rivaroxaban (23%) was most preferred when ischaemic events were rated worse than haemorrhagic events. Conclusion: New oral anti-coagulants had a more favourable benefit–risk profile across a wide range of assumptions regarding the relative importance of clinical events. Differences between NOACs were modest and depended upon the order of ranking of clinical events.